A study of the pharmacokinetics and thromboxane inhibitory activity of a single intramuscular dose of carprofen as a means to establish its potential use as an analgesic drug in white rhinoceros. Issue 4 (24th April 2018) - Leiberich, M.; Krebber, R.; Hewetson, M.; Marais, J.; Naidoo, V.
Abstract : The alleviation of pain and prevention of suffering are key aspects of animal welfare. Unfortunately, analgesic drugs are not available for all species. White rhinoceros ( Ceratotherium simum ), representing one of such species, which survive poaching attempts inflicted with severe facial injuries and gunshot wounds, nonetheless require analgesic support. To improve treatment conditions, this study explored the use of carprofen for the treatment of pain and inflammation in white rhinoceros. The pharmacokinetics of 1 mg/kg intramuscular carprofen was evaluated in six healthy white rhinoceros. The half‐life of λ z and mean residence time was 105.71 ± 15.67 and 155.01 ± 22.46 hr, respectively. The area under the curve and the maximum carprofen concentration were 904.61 ± 110.78 μg ml −1  hr −1 and 5.77 ± 0.63 μg/ml, respectively. Plasma TXB2 inhibition demonstrated anti‐inflammatory properties and indicated that carprofen may be effective for a minimum of 48 hr in most animals. With its long half‐life further indicating that a single dose could be effective for several days, we suggest that carprofen may be a useful drug for the treatment of white rhinoceros.